2021
DOI: 10.1186/s40545-021-00382-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of pharmacists’ readiness during coronavirus pandemic: the case of United Arab Emirates

Abstract: Background With the outbreak of Coronavirus infection (COVID-19), pharmacists play an important role in supporting local health during this emergency. Aim To assess the knowledge and to identify information sources regarding COVID-19 used by pharmacists, to investigate the active and public perceived roles of pharmacists, to explore the role of the pharmacy facilities and health authorities, and to identify barriers that would hinder pharmacists fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 11 Research in other countries, such as the United Arab Emirates also showed a positive attitude among pharmacists as to their role during pandemics. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 11 Research in other countries, such as the United Arab Emirates also showed a positive attitude among pharmacists as to their role during pandemics. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Some of the pharmacists thought that hydroxychloroquine has been used as a preventive therapy against the COVID-19 infection, which is similar to the previous findings. 19 Chloroquine or Hydroxychloroquine in addition to ventilatory support have been trailed by specialists in the management of hospitalised COVID-patients. 19 Many pharmacists were aware that azithromycin and hydroxychloroquine were used together for the treatment of COVID-19 infection, while merely 49% knew that antivirals such as oseltamivir, have been used in the management of coronavirus infection cases.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Chloroquine or Hydroxychloroquine in addition to ventilatory support have been trailed by specialists in the management of hospitalised COVID-patients. 19 Many pharmacists were aware that azithromycin and hydroxychloroquine were used together for the treatment of COVID-19 infection, while merely 49% knew that antivirals such as oseltamivir, have been used in the management of coronavirus infection cases. 22 Many pharmacists agreed that using NSAIDs such as Ibuprofen may increase the risk of COVID-19 complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey was developed after an extensive literature review [ 18 , 21 , 22 ]. Initially, a group of hospital and community pharmacists were contacted to suggest a list of the most common drugs and drug groups to which they have noticed an increase in their demand during COVID-19 and to provide any other comments they have observed related to medication demand.…”
Section: Methodsmentioning
confidence: 99%